Subsistence economy in the Negev Highlands: the Iron Age and the Byzantine/Early Islamic period. (April 2014) - Shahack-Gross, Ruth; Boaretto, Elisabetta; Cabanes, Dan; Katz, Ofir; Finkelstein, Israel
Abstract : The article reports results of a long-term geoarchaeological project in the Negev Highlands. Based on previous phytolith analysis from degraded livestock dung, we suggested that the inhabitants of an Iron IIA site in the region subsisted on animal husbandry, without practicing cereal cultivation (Shahack-Gross and Finkelstein 2008). Here we report on further investigations — on another Iron Age site, a Byzantine/Early Islamic site, and on a pre-modern Bedouin winter encampment. We seek to test the nature of the phytolith record in this arid environment. We establish that phytolith assemblages in the study area are generally well preserved; that phytolith concentrations in dung of pre-modern free-grazing livestock were originally low; and that in a Byzantine/Early Islamic site for which cereal cultivation is documented textually, livestock dung includes cereal phytoliths. These patterns enable a secure interpretation of the phytolith assemblages from the Iron IIA sites, fortifying our previous suggestion that the Iron Age inhabitants of the Negev Highlands subsisted mainly on herding and did not undertake dry farming.